(8-6i)-(-7+3i)=0

Simple and best practice solution for (8-6i)-(-7+3i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8-6i)-(-7+3i)=0 equation:



(8-6i)-(-7+3i)=0
We add all the numbers together, and all the variables
(-6i+8)-(3i-7)=0
We get rid of parentheses
-6i-3i+8+7=0
We add all the numbers together, and all the variables
-9i+15=0
We move all terms containing i to the left, all other terms to the right
-9i=-15
i=-15/-9
i=1+2/3

See similar equations:

| x/3-2/3=x/5 | | 3x+21=2x-3 | | 72(7x+24)=180 | | 81x^2-2=34 | | 2(3x-4)+10=5(x+4 | | 3(y-5)=-39 | | j+78/3=-6 | | x2.8=1.6 | | -986=f+1 | | 2y-39=-5(y-2) | | 26x+6=78 | | 44=2w+w | | 2k+2-k=10 | | 7y=6y-0.5 | | 27y=-837 | | s/5+21=26 | |  x+(x+1)=15 | | 0.5x^2-3x+18=14 | | 30=(c-91) | | 3x−6=-12 | | 9z-15=75 | | 180-x=1/3(x)+12 | | 5=k*7 | | 3x−6=-12=-12 | | v+23=99 | | 27=k*3 | | 6x^2-60x-1800=0 | | 50=k*7 | | X-14=9x+15 | | 1+2c=9 | | 7/6=x+4/8 | | 3/x=1/4 |

Equations solver categories